2022
DOI: 10.48550/arxiv.2205.15597
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Shock induced aerobreakup of a polymeric droplet

Abstract: Droplet atomization through aerobreakup is omnipresent in various natural and industrial processes. Atomization of Newtonian droplets is a well-studied area; however, non-Newtonian droplets have received less attention despite their frequent encounters. By subjecting polymeric droplets of different concentration to the induced airflow behind a moving shock wave, we explore the role of elasticity in modulating the aerobreakup of viscoelastic droplets. Three distinct modes of aerobreakup are identified for a wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The fragmentation of this liquid sheet accounts primarily for the generation of secondary droplets, whose size distribution is being measured in the present work. The mechanistic insights into the droplet breakup through SIE mode can be found in Sharma et al (2021) and Chandra et al (2022) and is not the focus of present work. Figure 2a, b shows the global overview of interaction dynamics for Weber number values of 879 and 4088, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The fragmentation of this liquid sheet accounts primarily for the generation of secondary droplets, whose size distribution is being measured in the present work. The mechanistic insights into the droplet breakup through SIE mode can be found in Sharma et al (2021) and Chandra et al (2022) and is not the focus of present work. Figure 2a, b shows the global overview of interaction dynamics for Weber number values of 879 and 4088, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…A detailed description of the experimental setup used for achieving shock-drop interaction can be found in previous work (Chandra et al 2022;Sharma et al 2021Sharma et al , 2022; however, the essential details of the test facility are also described here. The arrangement of equipment in a shock-droplet interaction setup is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to stretch the polymer chains, it is not only essential to have high strain rates but also accumulations of strains. 38,39 This indicates that polymeric fluids may behave as Newtonian fluids if the strains are smaller at early time scales. For coalescence, such observations are reported by Chen et al, 14 which is also reported by Dekker et al 20 However, our discussion is for a later timescale where the elasticity effects are predominant.…”
Section: Triggering Mechanisms For Coalescencementioning
confidence: 99%